Racism and censorship in the editorial and peer review process - Strauss, Dana; Gran-Ruaz, Sophia; Osman, Muna; Williams, Monnica T.; Faber, Sonya C. (Frontiers in Psychology, 2023)
Psychology aims to capture the diversity of our human experience, yet racial inequity ensures only specific experiences are studied, peer-reviewed, and eventually published. Despite recent publications on racial bias in research topics, study samples, academic teams, and publication trends, bias in the peer review process remains largely unexamined. Drawing on compelling case study examples from APA and other leading international journals, this article proposes key mechanisms underlying racial bias and censorship in the editorial and peer review process, including bias in reviewer selection, devaluing racialized expertise, censorship of critical perspectives, minimal consideration of harm to racialized people, and the publication of unscientific and racist studies. The field of psychology needs more diverse researchers, perspectives, and topics to reach its full potential and meet the mental health needs of communities of colour. Several recommendations are called for to ensure the APA can centre racial equity throughout the editorial and review process.